UPAYA MENANAMKAN NILAI-NILAI PROFETIK PADA ANAK USIA DINI MELALUI CERITA SIRAH NABAWIYAH: EFFORTS TO INSTILL PROPHETIC VALUES IN EARLY CHILDHOOD THROUGH STORIES OF SIRAH NABAWIYAH - Hidayati, Sri; Zulkarnain, Ali Iskandar; Ervina, Ervina; Saudah, Saudah; Muzakki, Muzakki; Aghnaita, Aghnaita; Afifah, Neela (Thufuli, 2024)
Sirah Nabawiyah is an existence that is targeted to be taught to children from an early age. This needs to be developed by instilling prophetic values, namely through the story of Sirah Nabawiyah. Especially for children at an early age who should be instilled and taught learning based on the Al-Qur'an and the Hadith of the Prophet. The aim of this research is to examine the instilling of prophetic values ​​in young children through the story of Sirah Nabawiyah. The research was conducted in a city in Palangka Raya, precisely in the province of Central Kalimantan, Indonesia. The research method used is qualitative. Data collection was obtained through observation, interviews and documents. The data analysis method uses the example of Miles, Huberman and Saldana which is carried out in three stages, namely data analysis by combining data, displaying data and drawing conclusions. The results of this research reveal that efforts to apply prophetic principles in childhood through the Sirah Nabawiyah story can contribute to the development of moral and religious values, language development, character formation and children's memory. The story of Sirah Nabawiyah for children is not only for knowing the story of Sirah Nabawiyah, but can increase children's love for the Prophet Muhammad SAW and learn about the Prophet's struggle in spreading the message of Islam, apart from that, children are also expected to be able to apply and emulate it in their daily lives.